Mechanical behaviour of steel hollow section columns subjected to damage – experimental study and finite element modelling - Larknath, Bijal (Department of Civil Engineering, 2025)
Hollow Steel Sections (HSS) are integral components in structural and architectural applications, valued for their torsional resistance, versatility, and aesthetic appeal. These welded steel tubes are typically manufactured off-site and transported to construction sites. However, during transportation, HSS members may incur damage, necessitating replacement in accordance with Sans 2001-CS1 (4.6.1.2) code specifications. This code outlines the criteria and procedures for assessing and replacing damaged HSS members, ensuring adherence to structural safety standards. This study aimed to assess the behaviour of HSS in response to damage. The objective was to determine the acceptability of commercially available damaged HSS structural specimens. Additionally, it investigated the possibility of retaining and repairing damaged Square Hollow Section members based on the extent of damage. Experimental testing, complemented by numerical models developed using ABAQUS software for finite element analysis, was employed to achieve these objectives. Various levels of damage were examined using both linear elastic and non-linear buckling analysis approaches. The results indicated a substantial reduction in the failure strength of the HSS members due to damage. However, the elastic buckling loads of the hollow sections were not significantly affected. This observation suggests a certain degree of tolerance in members that may be more prone to elastic buckling failure than material yield failure. The study acknowledges the potential development of a slenderness ratio specific to the buckling of damaged hollow sections, it ultimately recommends adherence to existing codes governing the repair and replacement of damaged hollow sections as well as provides a decision model based on utilisation of the damaged member. This pragmatic approach emphasises the importance of following established guidelines whilst also taking into consideration tolerances allowed for damaged members, in industry. The decision model provides practical guidance for the assessment and management of damaged HSS members in structural applications. In contrast to the stipulations in SANS Code 2001-CS1(2005), this model provides a selection criterion to either retain the specimen or replace/repair said damaged member.